2021
DOI: 10.3390/ijerph18094769
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Child-Appeal: The Development and Mixed-Methods Validation of a Methodology for Evaluating Child-Appealing Marketing on Product Packaging

Abstract: There is no standardized or validated definition or measure of “child-appeal” used in food and beverage marketing policy or research, which can result in heterogeneous outcomes. Therefore, this pilot study aimed to develop and validate the child-appealing packaging (CAP) coding tool, which measures the presence, type, and power of child-appealing marketing on food packaging based on the marketing techniques displayed. Children (n = 15) participated in a mixed-methods validation study comprising a binary classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…The lack of research into the power of outdoor food marketing is most likely a result of the lack of established definitions and classifications for the powerful characteristics of marketing and in particular, child appeal of marketing [ 123 ]. The most frequent persuasive creative strategies identified across the twelve studies documenting power were premium offers, promotional characters, health claims, taste appeals and emotional appeals, similar to those identified in television food marketing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of research into the power of outdoor food marketing is most likely a result of the lack of established definitions and classifications for the powerful characteristics of marketing and in particular, child appeal of marketing [ 123 ]. The most frequent persuasive creative strategies identified across the twelve studies documenting power were premium offers, promotional characters, health claims, taste appeals and emotional appeals, similar to those identified in television food marketing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…in colour, flavour, shape, or name [ 72 ]. In addition, the more different things were included on packaging increased the ‘interestingness’ of the product, and therefore its child-appeal [ 72 ]. Teens, on the other hand, may be drawn to elements like visual style (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[71] However, it has been argued that definitions of child-appeal should also include design elements like shapes, colours and sound. Mulligan et al (2021) found that children were drawn to packaging that were perceived as 'fun' , 'cool' , 'exciting' or 'interesting'; this included the concept of food or beverages being 'unconventional' , e.g. in colour, flavour, shape, or name [72].…”
Section: Implications For Mandatory Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among its various objectives, it seeks, through different management techniques, to capture the desired target’s attention and interest to improve sales opportunities ( 1 ). This is true for food products aimed specifically at children ( 2 ). The food industry is one of the most active marketing tools, as it operates on a saturated and competitive market ( 3 ).…”
Section: Introductionmentioning
confidence: 99%